2020
DOI: 10.1088/1757-899x/867/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of drought indices in the eastern Slovakia

Abstract: Extreme weather changes have been increasing in the recent times also in the eastern Slovakia. Extremely dry periods alternate with above-average precipitation. In the paper the drought indices were evaluated: Standardized Evapotranspiration Index (SPEI) and Standardized Precipitation Index (SPI). Using the non-parametric statistical Mann-Kendall test. The evaluated period was 1960 – 2015 at selected river and climatological stations in the eastern Slovakia. The results showed that no clean significant trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This means that the drought is increasing during the statistical period under study, also considering that in all the studied areas the value of the Z statistic is lower than 1.96, no significant trend has been observed at the 95% confidence level. Nagy et al (2020) found no significant trend in all the indicators (SPI and SPEI) when evaluating stations in Slovakia. Also, since the value of the Z statistic was negative during the study period (May, July, August, and September) in relation to remote sensing indicators such as NDVI, SAVI, and SR, there is a downward trend (reduction of vegetation and increase of drought).…”
Section: Resultsmentioning
confidence: 65%
“…This means that the drought is increasing during the statistical period under study, also considering that in all the studied areas the value of the Z statistic is lower than 1.96, no significant trend has been observed at the 95% confidence level. Nagy et al (2020) found no significant trend in all the indicators (SPI and SPEI) when evaluating stations in Slovakia. Also, since the value of the Z statistic was negative during the study period (May, July, August, and September) in relation to remote sensing indicators such as NDVI, SAVI, and SR, there is a downward trend (reduction of vegetation and increase of drought).…”
Section: Resultsmentioning
confidence: 65%
“…Meteorological and agricultural droughts have been considered by many authors (Karamuz et al, 2021;Łabędzki, 2015;Rimkus et al, 2020), but they defined drought mostly by drought indices. Also, authors in Slovakia analyse precipitation, meteorological and hydrological drought mainly on the basis of indices Jurík, Kaletová, 2018;Fendeková et al, 2018;Zuzulová, Šiška, 2017;Nagy et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, SPI is capable to identify drought and flood occurrences in a probabilistic manner (Blain, 2012). SPI is a commonly used metric for determining severe dryness or wetness (e.g., Bothe et al, 2010; Nagy et al, 2020; Santos et al, 2010; Sienz et al, 2012; Zhu et al, 2011). SPI is used in this study to analyze draught and flood at 10 precipitation stations located in the west part of Syria.…”
Section: Methodsmentioning
confidence: 99%